Pengaruh pengangguran dan gini ratio terhadap IPM di kabupaten deli serdang dengan ecm tahun 2003-2023 - Pane, Putri Marito; Sitinjak, Akase; Bangun, Belliyani Br; Saragih, Putri Damayanti; Manurung, Ulfa Nabilah (Universitas Muhammadiyah Enrekang, 2024)
This study analyzes the impact of unemployment and the Gini ratio on the Human Development Index (HDI) in Deli Serdang Regency from 2003 to 2023 using the Error Correction Model (ECM). The data used were obtained from the Central Bureau of Statistics (BPS). Classical assumption tests show no multicollinearity with VIF values below 10 and normality test results above 0.05. Long-term estimation results indicate that the Gini ratio has a probability value of 0.01 (< 0.05) and unemployment has a probability value of 0.04 (< 0.05). Additionally, in the short term, the probability for the unemployment variable also shows significant results below 0.05. These findings suggest that both unemployment and income inequality significantly impact HDI in the long and short term in Deli Serdang Regency.